PROTECTIVE ROLE OF ANTIBODIES IN TUBERCULOSIS AND HIV INFECTION - Нина Васильевна Мальцева (Медицина в Кузбассе)
The review discusses the protective humoral mechanisms in tuberculosis and HIV infection. These include the immunoglobulin Fc receptor (Fc receptor) mediated antibody effector functions leading to pathogen clearance, antibody-dependent cellular cytotoxicity, phagocytosis, and other defense responses. Both the isotype/class of protective antibodies and the expression and phenotype of Fc receptors determined by polymorphic genes on effector cells can be the basis for the implementation of these functions. Identification of the adaptability of specific antibodies and their immune complexes to polymorphic variants of Fc receptors for immunoglobulins is necessary to elucidate aspects of the formation of specific humoral immunity in infectious lesions, to obtain information for the development of new personalized approaches to the treatment of tuberculosis and HIV infection based on protective antibodies.